Vocational Anticipatory Socialization, Self-Determination Theory, and Meaningful Work: Parents' and Children's Recollection of Memorable Messages About Work. (August 2018) - Scarduzio, Jennifer A.; Real, Kevin; Slone, Amanda; Henning, Zachary
This study explored memorable messages that parents recall communicating and young adults recall receiving about meaningfulness and work, using the lens of self-determination theory (SDT). Analysis of 377 memorable messages revealed that such messages relate to the basic psychological needs underlying SDT competence, autonomy, and relatedness. Autonomy messages were the most commonly recalled by fathers' whereas mothers' messages aligned more with competence. Our research suggests implications for the important link between SDT and meaningful work in the context of parent–child relationships. Our theoretical implications extend the connections between the components of SDT and meaningful work and explore how parents' and young adults' match and mismatch.